From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Product distribution in hydrogenation of styrene oxide over Pd/chitosan catalyst - Viswanadhan, Maya; Potdar, Aparna; Divakaran, Anumon V.; Badiger, Manohar V.; Rode, Chandrashekhar (Research on Chemical Intermediates, 2016)
Palladium-decorated chitosan catalyst was synthesized by an impregnation method by varying the Pd loading in the range of 1-6 %, and was evaluated for the regioselective hydrogenation of styrene oxide. In order to correlate the chemical and textural properties with the catalytic activity, all the prepared catalysts were characterized by techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron spectroscopy, thermo-gravimetric analysis, temperature-programmed desorption of NH3, and CO2 and N-2 physisorption. The synthesized catalysts were utilized for the efficient and regioselective ring opening of styrene oxide by hydrogenation under different conditions. The complete conversion of styrene oxide with 65 % selectivity for 2-phenyl ethanol and 33 % for 1-phenyl ethanol were obtained using 4 % Pd/CS catalyst at 70 degrees C temperature and 3 MPa pressure. The mechanism for the regio selective ring opening of styrene oxide to 1- and 2-phenyl ethanol was also proposed on the basis of properties of the catalyst support, catalytic activity and selectivity. These results indicated that the catalytic activity and selectivity of the catalysts were affected by the nature of support. Further, the basic properties of the support play an important role in the selectivity of the styrene oxide hydrogenation reaction.

Cascade reductive etherification of bioderived aldehydes over Zr-based catalysts - Shinde, Suhas; Rode, Chandrashekhar (ChemSusChem, 2017)
An efficient one-pot catalytic cascade sequence has been developed for the production of value-added ethers from bioderived aldehydes. Etherification of 5-(hydroxymethyl)furfural with different aliphatic alcohols over acidic Zr-montmorillonite (Zr-Mont) catalyst produced a mixture of 5-(alkoxymethyl)furfural and 2-(dialkoxymethyl)-5-(alkoxymethyl)furan. The latter was selectively converted back into 5-(alkoxymethyl)furfural by treating it with water over the same catalyst. The synthesis of 2,5-bis(alkoxymethyl)furan was achieved through a cascade sequence involving etherification, transfer hydrogenation, and re-etherification over a combination of acidic Zr-Mont and the charge-transfer hydrogenation catalyst [ZrO(OH)(2)]. This catalyst combination was further explored for the cascade conversion of 2-furfuraldehyde into 2-(alkoxymethyl)furan. The scope of this strategy was then extended for the reductive etherification of lignin-derived arylaldehydes to obtain the respective benzyl ethers in >80% yield. Additionally, the mixture of Zr-Mont and ZrO(OH)(2) does not undergo mutual destruction, which was proved by recycling experiments and XRD analysis. Both the catalysts were thoroughly characterized using BET, temperature-programmed desorption of NH3 and CO2, pyridine-FTIR, XRD, inductively coupled plasma optical emission spectroscopy, and X-ray photoelectron spectroscopy techniques.

Facile one-pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers under mild conditions - Sakate, Sachin; Kamble, Sumit; Chikate, Rajiv; Rode, Chandrashekhar (Supramolecular Chemistry, 2017)
We report here the facile, room temperature, catalyst free, one pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers. Anhydrous potassium carbonate (K2CO3) as a mild base along with dimethyl sulfoxide generates the phenoxide ion which facilitates the nucleophilic substitution of bromoalkanes to yield the corresponding crown ethers.

Microwave-assisted synthesis of 5-substituted 1H-tetrazoles via [3+2] cycloaddition over a heterogeneous Cu-based catalyst: application to the preparation of N-13-labelled tetrazoles - Joshi, Sameer M.; Mane, Rasika B.; Pulagam, Krishna R.; Gomez-Vallejo, Vanessa; Llop, Jordi; Rode, Chandrashekhar (New Journal of Chemistry, 2017)
The [3+2] cycloaddition between various nitriles and sodium azide proceeds smoothly in the presence of a new Cu-II catalyst in N-methyl-2-pyrrolidone (NMP) to give the corresponding 5-substituted 1H-tetrazoles. The desired tetrazoles were obtained in high yields within 3-30 min by employing controlled microwave heating. The reaction most probably proceeds through the activation of the nitrile groups by the Cu-II species, followed by a successive [3+2] cycloaddition with the sodium azide. The good performance of the catalyst enabled the preparation of selected tetrazoles labelled with the positron emitter nitrogen-13 even under conventional heating. The short reaction time, simple work-up procedure, and recyclability of the catalyst are advantages of the method reported here.

Solvent-free glycerol transesterification with propylene carbonate to glycerol carbonate over a solid base catalyst - Kondawar, Sharda; Rode, Chandrashekhar (Energy & Fuels, 2017)
Glycerol transesterification using propylene carbonate (PC) to glycerol carbonate.(GC) could be efficiently performed under solvent-free 'conditions 'wing solid base as catalysts involving non-noble metal oxide in combination with hydrotalcites (HTs). Among all of the catalysts studied for transesterification, the best result was obtained over a calcium-doped hyclrotalcite (Ca-FIT) catalyst, giving 84% conversion of glycerol and almost complete. GC selectivity. The crystal structure of HT was modified by incorporation of Ca and La into FIT, as revealed by X-ray diffraction studies. The temperature-programmed desorption of carbon dioxide study confirmed the presence of the highest basic site density in terms of 1.94 mmol of CO2 desorbed/g of catalyst, responsible for its higher transesterification efficiency of the Ca-HT catalyst. The Fourier transform infrared spectroscopy study showed peaks at 3036 and 3042 cm(-1) for Ca -HT and lanthanum-doped hydrotalcite (La -HT), respectively, confirming the presence of hydrogen bonding between water and interlayer carbonate anions responsible for abstracting proton from the primary hydroxyl group of glycerol to attack over carbonyl carbon of PC. The presence of intercalated carbonate ions is also confirmed by the Raman study, in both PIT and ca-HT catalysts and even after use of the Ca HT catalyst. The thermogravimetry-differential thermal analysis study evidenced the higher thermal stability of the Ca -HT (T-4 = 765 degrees C) catalyst than that of parent HT with a Mg/Al ratio of 3:1 (T4 = 630 degrees C). Various process conditions, such as the temperature, molar ratio of glycerol/PC, and catalyst loading, significantly influenced conversion and selectivity of glycerol: and GC, Tespectively.

Cascade synthesis of 5-(Acetoxymethyl) furfural from carbohydrates over Sn-mont catalyst - Shinde, Suhas; Deval, Kashmira; Chikate, Rajeev; Rode, Chandrashekhar (ChemistrySelect, 2018)
The 5-(Acetoxymethyl)furfural (AcMF) is emerged as an important alternative for 5-(hydroxymethyl)furfural (HMF). It is also a starting material for those products which are typically prepared from HMF. The growing importance of AcMF encouraged us to prepare it directly from cheap and abundant carbohydrates. The production AcMF from glucose and glucose-like carbohydrates is an exigent assignment, owing to tough isomerisation of glucose to fructose. The Sn-Mont catalyst having a unique combination of Lewis as well as Bronsted acid sites was employed for direct glucose conversion into AcMF. Lewis acid sites of Sn-Mont facilitate the isomerisation of glucose to fructose. At the same time, dehydrative-esterification of fructose to AcMF is catalyzed by Bronsted acid sites of Sn-Mont. Different concentrations of Sn containing Sn-Mont catalysts were by prepared mixing montmorillonite clay with different molar concentration (e.g. 0.1 M-0.4 M) of aqueous solutions of SnCl4 center dot 5H(2)O. AcMF was produced in as high as 43% yield directly from glucose over Sn-Mont(0.3 M) catalyst owing to its highest acid strength. The efficacy of Sn-Mont(0.3 M) catalyst was also probed for sucrose and fructose that resulted in 53% and 58% yield of AcMF, respectively. The critical properties of all the prepared Sn-Mont catalysts were investigated through XRD, BET surface area, ICP-OES, temperature-programmed desorption of NH3 and pyridine-FTIR and XPS techniques.
Keywords: 5-(Acetoxymethyl)furfural; Bronsted/Lewis acid; carbohydrates; Dehydrative-esterification; Sn-Mont

Mixed bacterial culture mediated direct conversion of bio-glycerol to diols - Parate, Roopa; Mane, Rasika; Dharne, Mahesh; Rode, Chandrashekhar (Bioresource Technology, 2018)
Direct and economic transformation of biodiesel derived crude glycerol is gaining more significance. During screening of bacterial cultures Klebsiella pneumoniae and Enterobacter aerogenes were able to convert crude bio-glycerol to 2,3-butanediol (2,3-BDO) and 1,3-propanediol (1,3-PDO), as major compounds, ethanol and acetoin as minor compounds, with a conversion of 69% and 79% respectively. Process optimization could achieve maximum conversion at pH 7.0, 37 degrees C, 30-40 g/L glycerol and 1.5 g of inoculum until 120 h. Mixed cultures led to complete glycerol conversion with optimal yield and productivity. An innovative approach of using crude glycerol for sustained growth and tolerance of bacteria as source of carbon and energy makes this study more significant. In addition to this, a mixed culture concept introduced here is expected to make impact in process economics for industrial scale synthesis for direct transformation of glycerol into C3 and specifically, C4 diols.
Keywords: 1; 2; 3-Butanediol; 3-Propanediol; Bioconversion; Bioglycerol; Mixed culture

Crystalline LaCoO3 perovskite as a novel catalyst for glycerol transesterification - Phadtare, Deepshree; Kondawar, Sharda; Athawale, Anjali; Rode, Chandrashekhar (Molecular Catalysis, 2019)
LaCoO3 perovskite was synthesized using sol-gel method by nitrate and acetate precursors of La and Co with varying molar ratios of La and Co (1:1, 1:2 and 2:1). This was found to be an unique strategy to obtain highly crystalline LaCoO3 perovskite material without using any chelating agent. The variation of precursors was found to influence their crystallinity however, variation in molar ratio in the range of 0.5-2, did not affect the formation of perovskite framework. The formation of pure perovskite phase (around or > 80%) could be achieved by combination of acetate and nitrate precursors while, the combination of acetate- acetate or nitrate- nitrate precursors resulted in low phase purity for the perovskite due to the formation of secondary phases like La2O3 and Co3O4. Very interestingly, such combination of perovskite and pure oxide phases contributed to enhancement of basic sites which catalyzed the glycerol transestrifiaction with DMC (dimethyl carbonate) to GC (glycerol carbonate) and GD (glycidol). Among all the catalysts studied, NAP-2 showed highest efficiency in terms of 98% glycerol conversion and 77% GC and 22% GD selectivities. The highlight of this work is that first step glycerol transesterification with DMC required basic sites of either metal oxide or perovskite but for cascade reaction involving decarboxylation required both metal oxide as well as LaCoO3 perovskite phase.

Efficient bifunctional reactivity of K-doped CrO(OH) nanosheets: exploiting the combined role of Cr(iii) and surface -OH groups in tandem catalysis - Vernekar, Dnyanesh; Ratha, Satyajit; Rode, Chandrashekhar; Jagadeesan, Dinesh (Catalysis Science & Technology, 2019)
This work reports the bifunctional catalytic activity of layered K-doped alpha-CrO(OH). The combined action of the redox active Cr(III) and the surface hydroxyl groups was efficiently used to carry out 2-3 oxidation reactions in tandem followed by condensation/coupling reactions in one pot. Oxidation of benzyl alcohol followed by Knoevenagel condensation or coupling reactions forming C-C and C-N linkages in one pot is demonstrated. The catalyst has been characterized using XRD, IR, TGA, CO2-TPD, cyclic voltammetry, XPS and microscopic techniques to gain insight into the nature of active sites. The role of O- and O2- on the CrO(OH) catalyst in the bifunctional activity was studied using analytical techniques. Recyclability and leaching tests confirmed that K-alpha-CrO(OH) is a stable and environmentally safe catalyst.

Pyridine immobilised on magnetic silica as an efficient solid base catalyst for Knoevenagel condensation of furfural with acetyl acetone - Tarade, Komal; Shinde, Suhas; Sakate, Sachin; Rode, Chandrashekhar (Catalysis Communications, 2019)
Novel heterogeneous pyridine immobilised magnetic silica (Fe3O4@SiO2-Py) was found to be an efficient, greener and heterogeneous solid base catalyst for the Knoevenagel condensation of furfural with acetylacetone under optimized reaction conditions. The Knoevenagel condensation product 3-(2-furylmethylene)-2,4-pentanedione (FMP), a jet fuel precursor, was produced in high yield of 85% with 94% conversion of furfural at 100 degrees C within a period of 4 h. Fe3O4@SiO2-Py catalyst showed excellent stability and recyclability without losing its initial activity.
Keywords: furfural; Jet fuel; Knoevenagel condensation; Silica immobilised pyridine; Solid base

Integration of heterogeneous acid and base catalysis for clean synthesis of jet-fuel precursor from carbohydrates - Shinde, Suhas; Tarade, Komal; Mitra, Gaurav; Rode, Chandrashekhar (ChemistrySelect, 2020)
C-12 branched alkane fuel precursor was produced from carbohydrates using an efficient integrated solid acid and base catalysis approach involving: i) isomerisation-dehydration of carbohydrates to 5-(hydroxymethyl)furfural (HMF) over solid acid catalyst having both Lewis and Bronsted sites) in a biphasic MIBK (methylisobutylketone): water + DMSO solvent system and ii) Claisen-Schmidt condensation of crude HMF with MIBK over solid base catalyst. Initially, high yield of jet fuel precursor, (E)-1-(5-(hydroxymethyl)furan-2-yl)-5-methylhex-1-en-3-one from pure HMF and MIBK was achieved over basic CaMgAl(231) catalyst. The glucose dehydration to HMF was optimized in biphasic MIBK: H2O-NaCl: DMSO (8:1.5:0.5; v/v/v) system, with complete glucose conversion and 42% HMF yield over Zr-Mont possessing both Lewis and Bronsted acid sites. In an integrated dehydration + Claisen-Schmidt condensation sequence, Zr-Mont catalyst was filtered off and the crude HMF with MIBK underwent Claisen-Schmidt condensation over CaMgAl(231) catalyst. The overall 32% yield of Claisen-Schmidt condensation product was achieved from glucose. MIBK acting also as a product extractant, could be recovered upto 80%.
Keywords: Claisen-Schmidt condensation; dehydration; integrated; jet-fuel precursor; renewable

Magnetically separable catalyst for condensation of renewable aldehydes and 2-methylfuran to saturated cyclic oxygenates - Tarade, Komal; Shinde, Suhas; Rode, Chandrashekhar (Fuel Processing Technology, 2020)
The saturated cyclic ethers produced from biomass derived aldehydes and 2-methylfuran are the potential diesel fuel candidates. The synthesis of saturated cyclic ethers is a two step process which involves acid catalyzed condensation of aldehydes with 2-methylfuran and the subsequent selective furan ring hydrogenation of the condensation products. Here, we designed a novel recyclable magnetic solid acid catalyst such as [Fe3O4@SiO2-Pr-Py-H][2HSO(4)(2-)] and employed for the condensation of 2-methylfuran with formaldehyde as model substrates and reaction parameters were optimized. Under the set reaction conditions, condensation of 2-methylfuran with several other aldehydes were also successfully achieved with very good yields. Further, several supported noble metal catalysts were screened in order to find suitable catalyst system for selective furan ring hydrogenation of condensation products. Among those, 5% Pd/C was found to be very active and selective for furan ring hydrogenation without formation of ring opened products under very low hydrogen pressure at room temperature. Prepared catalysts were thoroughly characterized with sophisticated techniques.
Keywords: fuel additives; Hydrogenation; Hydroxyalkylation-alkylation; Magnetic solid acid; Organosilica

Synthesis of silver nanoparticles colloids in imidazolium halide ionic liquids and their antibacterial activities for gram-positive and gram-negative bacteria - Patil, Virendra; Mahajan, Swapnil; Kulkarni, Mohan; Patil, Kashinath; Rode, Chandrashekhar; Coronas, Alberto; Yi, Gi-Ra (Chemosphere, 2020)
Four 1-butyl-3-methylimidazolium halide ionic liquids were synthesized via metathesis and anion exchange reactions. Silver nanoparticles (AgNPs) colloids were synthesized in four ionic liquids in the pressurized reactor by reduction of silver nitrate with hydrogen gas, without adding solvents or stabilizing agents. Antibacterial activities of base ionic liquids and AgNPs colloids in ionic liquids were reviewed by well-diffusion method for gram-positive Bacillus cereus (NCIM-2155) and gram-negative Escherichia coli (NCIM-2931) bacteria. Antibacterial activities of ionic liquids and AgNPs colloids in ionic liquids were observed to be controlled by ionic liquids anions and AgNPs particle size. The 1 -butyl-3-methylimidazolium iodide ionic liquid exhibited higher antibacterial activities among the studied ionic liquids. Further, the presence of AgNPs in 1-butyl-3-methylimidazolium iodide, ionic liquid enhanced its antibacterial activity for Bacillus cereus and Escherichia coli bacteria. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Anion effect; antibacterial activity; Imidazolium halides; ionic liquids; silver nanoparticles

Bioglycerol (C3) upgrading to 2,3-butanediol (C4) by cell-free extracts of Enterobacter aerogenes NCIM 2695 - Parate, Roopa; Borgave, Mrunal; Dharne, Mahesh; Rode, Chandrashekhar (Journal of Chemical Technology and Biotechnology, 2021)
BACKGROUND Production of biobased chemicals from renewable resources is a green starring approach that serves as a substitute to petroleum derivatives. Bioglycerol, with its growing production as a co-product of biodiesel, is an attractive low-cost feedstock for the synthesis of platform chemicals by microbial fermentation. 2,3-butanediol (2,3-BDO) is amongst the top biorefinery platform chemicals that can be produced by glycerol fermentation. RESULTS The `Circular Economy' concept is demonstrated by converting the by-product bioglycerol using a cell-free extract of Enterobacter aerogenes NCIM 2695 (National Collection of Industrial Microorganisms, NCIM), yielding 22 g L-1 2,3-BDO, in 96 h, 98% atom economy and 0.4 g/g E factor. The cell-free bioglycerol conversion to 2,3-BDO was proved using a modified procedure for determining glycerol dehydrogenase enzyme assay by protein analysis and it was also shown to be cell-bounded. CONCLUSION Our study offers an effective utilization of the leftover material (i.e. cell-free extract) that biocatalysed C3 to C4 diol, which adds value to the overall economics of the process using only crude glycerol (C3) itself as a fermentative medium.
Keywords: 2; 3-Butanediol; atom economy; circular economy; E factor; Glycerol; glycerol dehydrogenase

Mechanical properties of anodic titanium dioxide nanostructures - Kulkarni, Mukta; Sepitka, Josef; Junkar, Ita; Bencina, Metka; Rawat, Niharika; Mazare, Anca; Rode, Chandrashekhar; Gokhale, Suresh; Schmuki, Patrik; Daniel, Matej; Iglic, Ales (Materiali in Tehnologije, 2021)
Highly ordered and uniform titanium dioxide (TiO2) nanotubes (NTs) with different morphologies (15 nm, 50 nm and 100 nm in diameter) were prepared by the electrochemical anodization of Ti substrates. The TiO2 NTs' surface properties were characterized by X-ray diffraction (XRD) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). The elastic modulus (E) and the Vickers hardness (HV) of the Ti foil and of the different-morphology TiO2 NTs were evaluated with the nano-indentation technique. E and HV increase with the decreasing length/diameter of the NTs, meaning that NTs with smaller diameters are more resistant to mechanical wear. The elastic modulus of the TiO2 NTs with 15-nm and 50-nm diameters is similar to that of the human bone.
Keywords: Elastic modulus; mechanical properties; titanium dioxide (TiO2) nanotubes; Vickers hardness

Role of preparation parameters of Cu-Zn mixed oxide catalyst in solvent free glycerol carbonylation with urea - Charate, Shrinivas; Shinde, Suhas; Kondawar, Sharda; Desai, Uday; Wadgaonkar, Prakash; Rode, Chandrashekhar (Journal of the Indian Chemical Society, 2021)
Solvent-free carbonylation of glycerol with urea to glycerol carbonate (GC) was achieved over heterogeneous Cu-Zn mixed oxide catalyst. Cu-Zn catalysts with different ratios of Cu:Zn were prepared using co-precipitation (CP) and oxalate gel (OG) methods. As compared to CuO-ZnO(2:1) catalyst prepared by oxalate gel (OG) method, much higher conversion of glycerol and highest selectivity towards glycerol carbonate (GC) was achieved with CuO-ZnO_CP(2:1) catalyst. Physicochemical properties of prepared catalysts were investigated by using XRD, FT-IR, BET, TPD of CO2 and NH3 and TEM techniques. The effect of stoichiometric ratio of Cu/Zn, calcination temperature of CuO-ZnO catalysts and effect of reaction parameters such as molar ratio of substrates, time and temperature on glycerol conversion to GC were critically studied. Cu/Zn of 2:1 ratio, glycerol-urea 1:1 molar ratio, 145 degrees C reaction temperatures were found to be optimized reaction conditions to achieve highest glycerol conversion of 86% and complete selectivity towards GC. The continuous expel of NH 3 from reaction the mixture avoided formation of ammonia complex with CuO-ZnO catalyst. As a result of this, CuO-ZnO catalyst could be recycled up to three times without losing its initial activity.
Keywords: Co-precipitation (CP); Glycerol; Glycerol carbonate; Oxalate gel (OG)

Influence of catalyst reduction temperature on autogenous glycerol hydrogenolysis over NiAl catalyst - Pandya, Rajan; Mane, Rasika; Rode, Chandrashekhar (Asian Journal of Organic Chemistry, 2022)
Autogenous glycerol hydrogenolysis to 1,2-propanediol by aqueous phase reforming (APR) was investigated over supported nickel catalysts. Effect of reduction temperature on physico-chemical properties of catalysts played a significant role in tuning conversion and product selectivities. The formation of nickel aluminate (NiAl2O4) spinel phase during catalyst reduction led to rearrangement of Ni species to obtain small and stable Ni particles. The catalyst activation temperature alters the extent of reduction of multivalent Ni species (Ni-0, Ni+2/+3) which facilitated glycerol dehydration and hydrogenation while suppressing C-C cleavage and thus avoiding undesirable side products. Additionally, presence of moderate Bronsted/Lewis acid ratio of the catalyst promoted higher 1,2-PDO selectivity. In-situ glycerol hydrogenolysis involves glycerol dehydration to acetol with simultaneous reforming to H-2 and CO2 and this hydrogen converts acetol to 1,2-PDO.
Keywords: APR; autogenous hydrogenolysis; Glycerol; Propanediols; reduction temperature; spinel

Ionic liquids for the sustainable transformation of levulinic acid to gamma-valerolactone (GVL) - Kondawar, Sharda; Rode, Chandrashekhar (Current Opinion in Green and Sustainable Chemistry, 2022)
This short review is focused on recent findings on the role of ionic liquids (ILs) in catalysing the hydrogenation of levulinic acid (LA) to gamma valerolactone (GVL), which is a cascade reaction involving more than one type of reaction. A brief introduction on green aspects of IL as a catalyst followed by various types of ILs being used for hydrogenation of LA to GVL are discussed. The unique characteristics of ILs responsible for hydrogenation reaction are also explained along with the current and upcoming scenario of IL catalysed hydrogenation of LA to GVL.
Keywords: Biomass; Gamma valerolactone; Hydrogenation; Ionic liquid; levulinic acid

Review on non-noble metal catalysts for glycerol hydrodeoxygenation to 1,2-propanediol with and without external hydrogen - Mane, Rasika; Jeon, Yukwon; Rode, Chandrashekhar (Green Chemistry, 2022)
The depleting petroleum oil resources, political embargos, and global warming dilemma have made it mandatory to develop alternative green technologies for energy and chemical production. Glycerol is one of the top-12 building block chemicals that can be mainly obtained as a coproduct of biodiesel production. The value addition of glycerol is only possible through its conversion to commodity and fine chemicals. Glycerol hydrogenolysis is one of the crucial pathways to produce several value-added products, among which 1,2-propanediol (1,2-PDO), 1,3-propanediol (1,3-PDO), ethylene glycol (EG) and 1-and/or 2-propanols are hydrogenolysis products. Selective glycerol hydrogenolysis to the desired product 1,2-PDO is only possible through the catalyst having an optimum combination of acid/base and metal sites (metallic and mixed oxides). The present review mainly focuses on the critical assessment of the influence of different supports, catalyst preparation methods, and/or pretreatment on structural, and electronic properties and simultaneously on the activity and product selectivity of non-noble metal catalysts. The role of reaction parameters in this industrially important reaction on catalyst performance will also be presented. A rigorous survey of patented literature on non-noble metal-catalyzed glycerol hydrogenolysis to 1,2-PDO is also discussed. Further, the review covers recent progress on non-noble metal-catalyzed autogenous glycerol hydrogenolysis through glycerol aqueous phase reforming (APR) and/or catalytic transfer hydrogenolysis (CTH), to overcome the cost and handling issues of external hydrogen. Finally, techno-economic analysis is also presented which compares the glycerol hydrogenolysis with and without external hydrogen with the conventional process of 1,2-PDO production. This analysis indicated that CTH and glycerol hydrogenolysis under ambient hydrogen pressure have the potential for commercialization, however catalyst stability and elimination of co-product formation at higher glycerol concentration need to be considered critically.

Calcination temperature impacting the structure and activity of CuAl catalyst in aqueous glycerol hydrogenolysis to 1,2-propanediol - Mane, Rasika; Potdar, Aparna; Jeon, Yukwon; Rode, Chandrashekhar (Topics in Catalysis, 2024)
This study investigated the impact of calcination temperature on the structural properties of CuAl catalyst which was found to be a robust nano-structured catalyst calcined directly without ramping at 400 °C and performed exceedingly well for aqueous phase hydrogenolysis of glycerol. Various samples of CuAl catalysts were prepared by co-precipitation at Cu: Al molar ratio 1:1 and were calcined at different temperatures (300–1000 °C). The obtained catalysts were reduced at 200 °C before their activity testing for glycerol hydrogenolysis reaction. To correlate the structure-activity, the catalysts were thoroughly characterized by XRD, XPS, BET, TEM, H2-TPR, NH3-TPD, and pyridine FTIR. It was observed that with an increase in calcination temperature from 300 to 700 °C, the glycerol conversion also increased from 47 to 55% with 93% selectivity to 1,2-PDO. The better performance of these catalysts was mainly related to the predominant presence of Brønsted acid sites, an appropriate ratio of the Cu0 to CuAl2O4 + CuO (0.33) and CuAl2O4 to CuO phases (0.35), the existence of Cu2O phase and the smaller Cu0 particle size. It was shown that altering the ramping rate for the calcination temperature of 400 °C impacted the catalytic activity. The CuAl-400 (DC) (direct calcined) catalyst exhibited a maximum glycerol conversion of 60%.

CuNPs@Al2O3-cellulose composite for the ligand-free Suzuki cross-coupling reactions in batch and continuous flow process - Patil, Seema; Rajmane, Archana; Jadhav, Sanjay; Rode, Chandrashekhar; Kumbhar, Arjun (Journal of Organometallic Chemistry, 2024)
In the present work, we synthesized recyclable CuNPs@Al2O3-CELL composite from an inexpensive and commercially available synthetic reagent by a simple method. The catalyst was characterized by various techniques such as TGA (Thermogravimetric analysis), SEM (Scanning electron microscope), TEM (Transmission electron microscopy), XPS (X-ray photoelectron spectroscopy), EDS (Energy dispersive spectroscopy), and AAS (Atomic Absorption Spectroscopy). The composite was applied for the Suzuki coupling reactions in the batch and flow process. The aryl halides were easily coupled with arylboronic acids in 95 % ethanol at 78 C. We systematically investigated the role of reaction temperature, solvent, and catalyst loading, on the transient and steady-state behavior of the flow reactor through an automated flow chemistry platform. The CuNPs@Al2O3CELL catalytic particles demonstrate minimal deactivation and leaching over a continuous Suzuki coupling reaction at a 20 min nominal residence time at 100 C. Moreover, the catalyst can be recovered by simple filtration and reused at least five times with a moderate decrease in product yield. The excellent activity and stability of the catalyst have been attributed to the strong chelation of the Cu species with hydroxyl functional groups of the Al2O3-CELL composite. The catalytic system was highly efficient in Suzuki coupling of various aryl bromides with different aryl boronic acids, yielding good to excellent product yields (80-96 %) with a TON of 15.914-19.066 and TOF of 2.649-9.533 h(-1).
Keywords: Continuous flow process; CuNPs@Al2O3-CELL; ligand-free; recyclable; Suzuki coupling

Magnetically separable Brønsted acid catalyst for the synthesis of Bisguaiacol-F - Tarade, Komal; Rode, Chandrashekhar; Kamble, Sanjay (New Journal of Chemistry, 2025)
Currently, polycarbonates, epoxy resins, and plastics are commercially made from Bisphenol-A. However, BPA-containing materials are well known for causing major health problems and have been banned in several countries. To address this concern, Bisguaiacol-F (BGF) has been developed as a safer and more sustainable alternative to Bisphenol-A. We created a novel sulfonic acid-functionalized, magnetically separable heterogeneous Br & oslash;nsted acid catalyst, [Fe3O4@SiO2-(Pr)3-N-Bu-SO3H][HSO4-], which was successfully utilized for the manufacture of BGF by condensing 37% aq. formaldehyde with two molecules of guaiacol. The main objective for this reaction was to avoid using excess guaiacol while also completing the conversion of both starting components. Surprisingly, our manufactured catalyst promotes the complete conversion of aqueous formaldehyde and guaiacol into regioisomers such as pp `-BGF, mp `-BGF and op `-BGF with 62%, 15%, and 6% selectivity, respectively. Our novel magnetically separable heterogeneous catalyst has improved catalytic activity in terms of starting material conversion and product distribution, which can be attributed to its unique structural characteristics. It contains a pendant -SO3H group that is connected to a lengthy butyl chain, making it conveniently accessible in the reaction. We have created the framework for a promising and environmentally aware approach to the synthesis of Bisguaiacol-F by meticulously optimizing reaction parameters such as time, temperature, reactant molar ratio, and catalyst loading. The catalyst was extensively characterized using acid-base titration, FT-IR, XRD, TGA, and NMR techniques to confirm the structure and reveal remarkable stability and activity. Notably, the catalyst demonstrated recyclability across six consecutive runs, with no noticeable reduction in its effectiveness. The catalytic activity was also tested for guaiacol condensation with a variety of aldehydes to create Bisguaiacol derivatives.